Verificação e quantificação em escala de bancada do volume de ar medido em igações prediais - Ney Lopes Procopio (2007)
The purpose of the present work is to evaluate the volume of air measured in domestic water supply pipe connections. It is a current problem as shown by a series of suits running in courts in several cities questioning that the amounts charged by the water supply companies might have been increased by air in the water distribution network. Due to the high level of interest generated by the matter, the present work will try to clarify some conflicting points through essays performed in a hydraulic laboratory counter which simulates a part of a distribution pipe connected to a domestic water supply pipe. Additionally, tests were performed toevaluate the efficiency and applicability of air reducing valves in domestic water supply connections, once the Act 12645/97 allows Minas Gerais water consumers to have the installation of such equipment. In addition to the evaluation of such devices, the efficiency of air release valves was checked, installed upstream the domestic water supply pipe at thehighest point of the water supply network. The results obtained under regular water supply conditions showed that the quantity of air in the water measured by the hydrometers is comparable to the one found in the environment water. On the other hand, the water supply, right after emptying the network connected to the domestic water supply pipe, revealed that the volume of water which gets to the gauged reservoir, comprehends 4% and 9% of the total air-water volume recorded by the hydrometer for the experiments performed in the test time interval of 180 seconds and a 10 mca pressure. For the same time interval, despite the 50 mca pressure, the volume of water varies from 6% to 21% of the total volume recorded by the hydrometer. By increasing the time interval to 300seconds, and keeping the pressure at 10 mca, the volume of water that effectively gets to the gauged reservoir is between 7% and 20% of the total volume recorded by the hydrometer. Such results show clearly the mistakes made by the hydrometer when measuring the twophaseoutflow of water and air. In order to evaluate the efficiency of the apparatus aimed at reducing the volume of air in the domestic water supply, three devices used to reduce the air carried along with the water were tested: air eliminator, air blocker and air release valve. Among the valves tested, the air eliminator presented the best performance in terms ofefficiency in the air withdrawal, especially for the smallest outflow. As to the air blocker, in addition to having a lower performance compared to the tested air eliminator, when blocking the air carried by the water supply network it can contribute so as the water pockets contained in the domestic water supply pipe return to the water supply network, thereforeinfluencing in the air registration through another measuring structure next to it. Concerning the other apparatus tested, the air release valve has lower performance than the air blocker and a lot lower than the air eliminator performance. As to the apparatus tested air eliminator, for discharges lower than 0.18 m3/h, the efficiency was 91% and 99% for pressures 0.5 MPa and 0.1 MPa, respectively. The results also revealedthat the hydrometer, even after being specified adequately for the consumption measured, in the presence of air, may operate out of the recommended range, causing its mechanism to wear down and mistakes higher than 5%. The results obtained cannot be generalized for water supply systems and it is still important to take into account that the volume of air measured in the experiments is peculiar of the testsbench. Therefore, as to the water supply networks, the volume of water carried into the water supply network will depend on the diameter and the pipes length and on the existence or not of devices aimed at eliminating the air out of such networks.